Reliability and Validity of the C-BiLLT: A new Instrument to Assess Comprehension of Spoken Language in young Children with Cerebral Palsy and Complex Communication Needs. - Geytenbeek, Joke J.; Mokkink, Lidwine B.; Knol, Dirk L.; Vermeulen, R. Jeroen; Oostrom, Kim J. (AAC: Augmentative & Alternative Communication, 2014)
In clinical practice, a variety of diagnostic tests are available to assess a child's comprehension of spoken language. However, none of these tests have been designed specifically for use with children who have severe motor impairments and who experience severe difficulty when using speech to communicate. This article describes the process of investigating the reliability and validity of the Computer-Based Instrument for Low Motor Language Testing (C-BiLLT), which was specifically developed to assess spoken Dutch language comprehension in children with cerebral palsy and complex communication needs. The study included 806 children with typical development, and 87 nonspeaking children with cerebral palsy and complex communication needs, and was designed to provide information on the psychometric qualities of the C-BiLLT. The potential utility of the C-BiLLT as a measure of spoken Dutch language comprehension abilities for children with cerebral palsy and complex communication needs is discussed.